Impact of food insecurity on cognitive health in older adults: insights from the NHANES 2011–2014 data - Zhang, Yanwei; Jiang, JiaWen; Yin, Dekun (Frontiers in Nutrition, 2024)
Abstract Purpose: To investigate the relationship between food insecurity and cognitive decline among elderly Americans. Methods: Utilizing NHANES 2011-2014 data, we examined cognitive function via the Immediate Recall Test (IRT), Delayed Recall Test (DRT), Animal Fluency Test (AFT)，Digit Symbol Substitution Test (DSST) and assessed food security through the U.S. Food Security Survey Module. Multiple regression models were used to adjust for demographic and health variables. Results: Food insecurity demonstrated a significant association with lower cognitive function scores. The effects of food insecurity on cognitive function were moderated by factors such as smoking and alcohol use, indicating a direct influence of food insecurity on cognitive decline. Conclusion: This study underscores the importance of food security for cognitive health in the elderly and advocates for targeted interventions to address nutritional disparities and enhance cognitive functioning in aging populations.